Studi Fenomenologi: Perilaku Konsumtif Game Online Pada Remaja di Kelurahan Siwalankerto Kota Surabaya Perspektif Maslahah - Muafi Aulia Rachman; Muhammad Lathoif Ghozali (ITB AAS INDONESIA Surakarta, 2023)
The development of technology and information has developed so rapidly and has progressed, be it in the business sector to the entertainment sector. With the internet, various activities can be done easily and quickly, including playing games as a means of entertainment for today's society. Online games are one of the platforms that are in great demand by the public because online games can be played using the internet network. This article aims to find out how the consumptive behavior of adolescents in buying virtual goods in online games, the research method used in this study is a qualitative method with a phenomonelogical approach by taking data sources through observation and interviews and secondary data sources through literature studies, mass media and social media. Research shows that the consumption behavior of teenagers in online games has become more wasteful, because the purchase of virtual goods is done to fulfill desires alone, not to meet their needs and aspects of benefit. This is very contrary to the concept of maslahah in Islam.